Prevalence, intensity and associated risk factors of soil-transmitted helminth infections among individuals living in Bata district, Equatorial Guinea. - Gertrudis Ribado Meñe; Jean Claude Dejon Agobé; Juan Carlos Momo Besahà; Florentino Abaga Ondo Ndoho; Salim Abdulla; Ayôla Akim Adegnika (Public Library of Science (PLoS), 2023)
Background Soil transmitted Helminths (STH) infections remain a public health concern worldwide, particularly in tropical and subtropical areas where these diseases are highly endemic. Knowing the prevalence and risk factors of the disease is crucial for efficient STH control strategies in endemic areas. The scarcity of epidemiological data on STH for Equatorial Guinea has motivated the decision to perform the present study. Methods A cluster-based cross-sectional study was carried out in Bata district from November 2020 to January 2021. Stool samples were collected for the diagnostic of STH infections using Kato-Katz technique. Descriptive statistics was performed for determination of STH prevalence and intensity, while logistic regression models were used to assess the risk factors associated with STH infections. Results A total of 340 participants were included in the study with a mean age of 24 years (SD = 23.7) and 1.2 female-to-male sex-ratio. The overall prevalence of any STH was 60% (95%CI: 55-65). The most prevalent species were Ascaris lumbricoides (43%, 95%CI: 37-48) and Trichuris trichiura (40%, 95%CI: 35-46). Intensity of infection were mainly light to moderate. A trend of association was observed between age and any STH infection (overall p-value = 0.07), with a significant difference observed between children aged 5-14 years as compared to those aged 1-4 (aOR 2.12; 95%CI: 1.02-4.43, p-value = 0.04), while locality was significantly associated with STH infection (overall p-value<0.001) with a higher odds observed for peri-urban area as compared to urban area (aOR 4.57; 95%CI: 2.27-9.60, p-value<0.001). Conclusion Bata district is a high STH transmission area, where school-aged children and peri-urban areas are associated with a higher risk of any STH infection. This situation calls for a full implementation of the WHO recommendations for STH control; mass drug administration of anthelminthic twice a year to the whole population with great attention to school age children, and prioritizing peri-urban areas where safe water, improve sanitation, and hygiene education should be implemented to achieve a better control.